A new variety of Phanera glauca subsp. tenuiflora (Leguminosae: Caesalpinioideae) from India - Kumar, Ramesh; Bandyopadhyay, Subir; Sharma, Sachin (Phytotaxa, 2014)
A new variety, Phanera glauca subsp. tenuiflora var. murlenensis, is described from Mizoram, India.